PENGEMBANGAN SISTEM MONITORING KEHADIRAN SISWA SECARA ONLINE DI LINGKUNGAN SEKOLAH BERBASIS ANDROID(Studi Kasus : MA Al-Istiqomah Rajadesa) - gina dewi sonia; Hasanudin; Cecep Abdul Cholik (Universitas Islam Al-Ihya Kuningan, 2025)
A common issue faced by every school institution is violations committed by students, such as truancy or non- compliance with school rules. This leads to a decrease in the students' discipline, causing harm to themselves and others, especially their parents. Students who commit violations will receive a warning letter to the Guidance and Counseling (BP/BK) teacher or a summons letter to their parents. As a result, parents are required to come to school to address the summons, and the BP/BK teacher will provide information, including a list of students who have committed violations or truancy, to the parents.The author offers a solution to address the issue of students who do not comply with school rules, such as truancy or manipulation of attendance records in class. The author has developed an application called the Online Student Attendance Monitoring System in the School Environment Based on Android (MA Al-Istiqomah Rajadesa). This Student Attendance Monitoring application is an Android app designed to facilitate teachers in taking attendance and providing information to parents about students' attendance data. The information provided by the teacher to the parents includes student attendance during class and helps parents monitor their child's learning progress while attending class. The application developed by the author is integrated with a database and provides information stored in the database about student attendance during school. This application is built using software for creating Android applications with Java programming language. The database commonly used in this Android operating system is Firebase